Sharpening enhancement technique for MR images to enhance the segmentation. (March 2018) - S., Jeevakala; A., Brintha Therese
Highlights: This method involves the LPSVD based sharpening enhancement technique. The LP decomposition augments the high-frequency content of the image using shape-invariant properties of edges. The SVD techniques enhance the contrast of edge pixels to bring out the boundary features. The subjective assessment parameters like PSNR, MSSIM, AMBE are used to evaluate the performance of the techniques. Abstract: This study presents a sharpening image enhancement technique based on the Laplacian pyramid (LP) and singular value decomposition (SVD) to improve the visibility and segmentation of subtle organs. The technique utilizes the shape-invariant properties of LP and the SVD techniques to enhance the perceptual sharpness of an image. The sharpening enhancement of magnetic resonance images not only sharpens the edges, but also reduces the noise effect. The results are compared with state-of-art enhancement techniques. The performance measures like peak-signal-to noise (PSNR), mean structural similarity index (MSSIM), and absolute mean brightness error (AMBE) evaluates the improved performance of the proposed technique.